2011
DOI: 10.1097/mca.0b013e32834d3346
|View full text |Cite
|
Sign up to set email alerts
|

Circulating neuregulin-1β levels vary according to the angiographic severity of coronary artery disease and ischemia

Abstract: Background Coronary artery disease (CAD) is the leading killer in the U.S. Patients with severe CAD and ischemia have worse prognosis. Therefore expansion of biomarker research, to identify at risk individuals and explain the complex biology between cardiovascular growth factors and atherosclerosis is needed. Neuregulin-1β (NRG-1β) is a myocardial stress activated growth and survival factor released from endocardial and endothelial cells. NRG-1β is essential for cardiovascular development and a regulator of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 19 publications
(27 reference statements)
4
33
0
11
Order By: Relevance
“…Ky et al reported that circulating NRG-1 levels are increased in chronic heart failure of ischemic but not of non-ischemic etiology (16). Geisberg et al reported plasma NRG-1β levels were statistically higher in patients with stress-induced ischemia, and NRG-1β levels were inversely correlated with ischemia severity (17). These findings suggest that ischemia may be an important trigger for endothelial NRG-1 synthesis and release.…”
Section: Discussionmentioning
confidence: 63%
“…Ky et al reported that circulating NRG-1 levels are increased in chronic heart failure of ischemic but not of non-ischemic etiology (16). Geisberg et al reported plasma NRG-1β levels were statistically higher in patients with stress-induced ischemia, and NRG-1β levels were inversely correlated with ischemia severity (17). These findings suggest that ischemia may be an important trigger for endothelial NRG-1 synthesis and release.…”
Section: Discussionmentioning
confidence: 63%
“…92 In patients with stable coronary disease without ischemia or heart failure, NRG-1β levels were inversely associated with coronary arterial disease severity. 93 Interestingly, NRG-1β levels were higher in patients with stress-induced ischemia. These results are consistent with the concept that myocardial NRG-1β is activated in response to ischemia as observed in the isolated heart.…”
Section: Role Of Nrg As a Potential Biomarkermentioning
confidence: 96%
“…higher NRG-1β levels in in class II and IV, compared to class I or II) (49). A subsequent study likewise found higher levels of NRG-1β in both plasma and serum of patients with coronary artery disease (CAD) who exhibited stress-induced ischemia (50). However, circulating levels of NRG-1β in stable CAD patients were found to be inversely correlated with angiographic severity of disease (50).…”
Section: Neuregulin As a Marker Of Cardiovascular Healthmentioning
confidence: 88%